Learning Obstacles of Prospective Madrasah Ibtidaiyah Teachers in Set Theory: A Praxeology Theory Review - Mimi Hariyani; Mazlini binti Adnan; Melly Andriani; Herawati Herawati; Suherman Suherman (CV. Creative Tugu Pena, 2026)
The identification of learning barriers is conducted to diagnose various problems encountered in learning so that the learning process becomes optimal. Set theory is one of the essential topics in the Basic Mathematics Concepts course taken by prospective Madrasah Ibtidaiyah teachers in the early semester. This study aims to identify and describe the learning barriers of prospective Madrasah Ibtidaiyah teachers in set theory based on praxeology theory. The approach used in this study is qualitative with a case study method. The participants of this study consisted of 37 prospective Madrasah Ibtidaiyah teacher education students from a teacher education institution in Pekanbaru, Riau, Indonesia. Data collection techniques used triangulation, consisting of tests and interviews. Based on the results of the analysis of students’ answers and in-depth interviews, learning barriers in set theory were found, including ontogenic, didactic, and epistemological barriers. These learning barriers can be seen from students’ limited knowledge, ranging from understanding set concepts, set operations, to set problem solving. These three types of learning barriers can serve as a reference for lecturers in designing didactic strategies that can minimize the learning barriers of prospective teachers in learning basic mathematics concepts, particularly in set theory.